Combining Ability of Quantitative Traits in Snake Gourd (Trichosanthes Cucumerina Var. Anguina) (Bangladesh Journal of Agricultural Research, 2023)
The present study was carried out on snake gourd having seven diverse genotypes (TC 01, TC 05, TC 24, TC 33, TC 02, TC 46 and TC 53) used as parental lines and their 21 crosses generated from 7 × 7 half-diallel fashion at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) during March to June 2019 following RCBD with three replications. The aim of the study was to determine general combining ability (GCA) and specific combining ability (SCA) for fruit yield and its related traits including fruit quality traits. General prediction ratio (GPR) of these 14 traits was greater than 0.5 (50%), indicating predominance of additive gene effects over non-additive gene effects. The estimates of GCA for 19 quantitative traits revealed that the genotypes P2 and P6 were good general combiners for promoting earliness as well as most other important characters viz., number of fruits/ plant, individual fruit weight and fruit yield/ plant/ hectare; P2 and P6 were also good for fruit length and fruit diameter, respectively whereas, P4 was good for main vine length and number of nodes on main vine while, P3 was superior for long fruit and 100-seed weight whereas, P5 was good for number of seeds/ fruit and P1 good for less fruit fly infestation including individual fruit weight and fruit length. The most promising specific combiners for fruit yield, quality and yield components were from the 13 crosses viz., P1 × P2, P1 × P3, P1 × P4, P1 × P7, P2 × P3, P2 × P5, P2 × P6, P2 × P7, P3 × P7, P4 × P5, P4 × P6, P4 × P7 and P5 × P7. Out of 13 crosses only two crosses namely, P1 × P2 and P2 × P6 had both the good general combiner parents (high × high). These two crosses were therefore, amenable for improvement of the respective traits through pedigree selection. Remaining 11 crosses displaying high SCA effects for different traits were observed to be derived from parents having various types of GCA effects (high × medium, high × low, medium × low and low × low). The results of 13 crosses therefore, indicate the operation of additive × additive, additive × dominant and/ or dominant × dominant gene interactions for the genetic control of expression of the relative traits.Bangladesh J. Agril. Res. 46(4): 491-510, December 2021